2021
DOI: 10.48550/arxiv.2101.05299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gamma-ray Thermalization and Leakage from Millisecond Magnetar Nebulae: Towards a Self-Consistent Model for Superluminous Supernovae

Indrek Vurm,
Brian D. Metzger

Abstract: Superluminous supernovae (SLSNe) are massive star explosions that are too luminous to be powered by traditional energy sources, such as the radioactive decay of 56 Ni. These transients may instead be powered by a central engine, such as a millisecond pulsar or magnetar, whose relativistic wind inflates a nebula of high energy particles and radiation behind the expanding supernova ejecta. We present three-dimensional Monte Carlo radiative transfer calculations of SLSNe which follow the production and thermaliza… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 96 publications
(153 reference statements)
0
9
0
Order By: Relevance
“…Recently, Vurm & Metzger (2021) presented the first radiative transfer models of magnetar-powered SN light curves, including the numerous photon-matter interactions that are possible in the magnetar wind nebula and expanding ejecta. They find that the thermalization opacity varies with time, and that the nebula magnetization strongly affects its evolution.…”
Section: Implications Of the Light Curve Flatteningmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Vurm & Metzger (2021) presented the first radiative transfer models of magnetar-powered SN light curves, including the numerous photon-matter interactions that are possible in the magnetar wind nebula and expanding ejecta. They find that the thermalization opacity varies with time, and that the nebula magnetization strongly affects its evolution.…”
Section: Implications Of the Light Curve Flatteningmentioning
confidence: 99%
“…This implies that substantial magnetic dissipation in the nebula is required to explain events like SN 2015bn and SN 2016inl. While a numerical model using the engine parameters relevant for SN 2016inl has not been calculated by Vurm & Metzger (2021), its shallower powerlaw decline likely indicates a higher degreee of magnetization than in SN 2015bn.…”
Section: Implications Of the Light Curve Flatteningmentioning
confidence: 99%
See 1 more Smart Citation
“…We treat γ b as a parameter, assuming γe ∈ [10 3 , 10 7 ], where γ b does not have to be the same as the bulk Lorentz factor of the wind. The pair multiplicity is model dependent, and cascades in the nebula and/or wind may contribute at early times (Murase et al 2015;Vurm & Metzger 2021). Also, it has been known that the radio data of the Crab nebula require large multiplicities (with ∼ 10 6 ) that are theoretically challenging (e.g., Arons 2012), which may originate from continuously-heated pairs that were injected in the past or from another component (Atoyan 1999;Tanaka & Asano 2017).…”
Section: The Lepton Injection Rate ṅInjmentioning
confidence: 99%
“…Murase et al (2015) showed that external inverse-Compton emission is important until SN photons mostly escape. Intriguingly, extremely small values of B are independently motivated by a possible solution to the missing energy problem for SN 2015bn and SN 2017egm (Vurm & Metzger 2021). As an example, we take B = 10 −6 , γ b = 10 3 , and q1 = 1 (in which the Compton parameter YIC 10).…”
Section: Model Implicationsmentioning
confidence: 99%